A survey exploring the nexus of psychological traits, nature connection, and quality of life among patients with rheumatoid arthritis - Eng Hui, Ellern; Ooi, Pei Boon; Chow, Sook Khuan; Hwang, Jung Shan; Peh, Suat Cheng; Teh, Jane Kimm Lii; Wu, Shin Ling; Wan Ghazali, Wan Syamimee; Ching, Siew Mooi (Taylor and Francis, 2024)
Background: As the recognition of psychological factors in chronic illness management grows, this study examined the interplay of psychological traits–grit, self-efficacy, resilience, and nature-relatedness–and their collective impact on the Quality of Life (QoL) among patients with rheumatoid arthritis (RA) in Malaysia. Methods: A cross-sectional study was conducted among 222 patients with RA at a private hospital in Malaysia. Utilizing validated scales, including the Connor-Davidson Resilience Scale, Short Grit Scale, Nature Relatedness Scale, and Arthritis Self Efficacy Scale, data were collected. Pearson Product-moment Correlation analyses assessed the relationships between variables, and a multiple mediation analysis explored the mediating effects of resilience, grit, and self-efficacy on the relationship between nature-relatedness and QoL. Findings: Of the 222 participants (86% female, mean age = 56.03, S.D. = 13.42), the analysis revealed a significant mediating role of resilience in the relationship between nature-relatedness and QoL among RA patients (b = −.117, SE =.042, 95% BCa CI [−.208, –.046]). Although grit and self-efficacy positively correlated with QoL, they did not serve as significant mediators in the nature-relatedness–QoL relationship. This highlights the pivotal role of building a sense of resiliency among patients with RA. Interpretation: Individuals with RA are not only resilient in terms of their psychological traits such as grit, self-efficacy, and general resilience but also exhibit resilience in their connection and interaction with the natural environment (nature-relatedness). This holistic concept recognizes that fostering resilience in both psychological aspects and the context of one's environment is crucial for promoting overall well-being, particularly in the management of chronic illnesses like RA. It emphasizes the interconnectedness of psychological factors and environmental engagement in contributing to an individual's ability to cope and thrive despite health challenges.